2018
DOI: 10.1186/s13014-018-1012-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of virtual block objects in reducing the lung dose in helical tomotherapy planning for cervical oesophageal cancer: a planning study

Abstract: BackgroundIntensity-modulated radiotherapy is useful for cervical oesophageal carcinoma (CEC); however, increasing low-dose exposure to the lung may lead to radiation pneumonitis. Nevertheless, an irradiation technique that avoids the lungs has never been examined due to the high difficulty of dose optimization. In this study, we examined the efficacy of helical tomotherapy that can restrict beamlets passing virtual blocks during dose optimization computing (block plan) in reducing the lung dose.MethodsFifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Thus, using the virtual contour shape in this study for a treatment plan in the DB mode for cervical esophageal cancer may keep the dose distribution changes that result from patient movement within a clinically acceptable level. In our previous study, we evaluated the dose reduction to the OARs and dose concentration to the targets using various virtual contour shapes; the virtual contour shape used in the present study was the one that scored the highest in the previous study, which was shown to be the most clinically useful for 20 patients . This virtual contour shape, a semicircle that follows the shape of the lung at a distance of 8 cm from the tracheal bifurcation, can effectively reduce the dose to OARs and provide safe delivery, even with patient movement, with the same PTV margin as the NB mode.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Thus, using the virtual contour shape in this study for a treatment plan in the DB mode for cervical esophageal cancer may keep the dose distribution changes that result from patient movement within a clinically acceptable level. In our previous study, we evaluated the dose reduction to the OARs and dose concentration to the targets using various virtual contour shapes; the virtual contour shape used in the present study was the one that scored the highest in the previous study, which was shown to be the most clinically useful for 20 patients . This virtual contour shape, a semicircle that follows the shape of the lung at a distance of 8 cm from the tracheal bifurcation, can effectively reduce the dose to OARs and provide safe delivery, even with patient movement, with the same PTV margin as the NB mode.…”
Section: Discussionmentioning
confidence: 98%
“…Figure (b) illustrates the DB mode, showing how beamlet A, which reached the virtual contour before passing through the PTV, is not included in the dose optimization process, whereas beamlet B, which reached the contour after passing through the PTV, is included. In our previous study, the DB mode with the virtual contour shape used in the present study could create treatment plans for 20 patients without any clinical problems . We therefore used the DB mode in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many methods for reducing the lung dose have been reported in dynamic arc radiotherapy 9 , 10 . However, the selection of gantry arc angle and dose constraints are the key factors in radiotherapy treatment planning (RTP).…”
Section: Introductionmentioning
confidence: 99%